The Role of O Plus and He Plus in the Propagation of Kinetic Alfven Waves in the Earth S Inner Magnetosphere - Pinto-Abarzua, V (IOP Publishing Ltd, 2022)
Interactions between plasma particles and electromagnetic waves play a crucial role in the dynamics and regulation of the state of space environments. From plasma physics theory, the characteristics of the waves and their interactions with the plasma strongly depend on the composition of the plasma, among other factors. In the case of the Earth s magnetosphere, the plasma is usually composed of electrons, protons, O+ ions, and He+ ions, all with their particular properties and characteristics. Here, using plasma parameters relevant for the inner magnetosphere, we study the dispersion properties of kinetic Alfven waves (KAWs) in a plasma composed of electrons, protons, He+ ions, and O+ ions. We show that heavy ions induce significant changes to the dispersion properties of KAWs, such as polarization, compressibility, and the electric-to-magnetic amplitude ratio, and therefore the propagation of KAWs is highly determined by the relative abundance of He+ and O+ in the plasma. These results, when discussed in the context of observations in the Earth s magnetosphere, suggest that for many types of studies based on theory and numerical simulations, the inclusion of heavy ions should be customary for the realistic modeling of plasma phenomena in the inner magnetosphere or other space environments in which heavy ions can contribute a substantial portion of the plasma, such as planetary magnetospheres and comet plasma tails.